Rethinking the State's Role in Finance - Čihák, Martin; Demirgüç-Kunt, Asli (World Bank, Washington, DC, 2013)
The global financial crisis has given greater credence to the idea that active state involvement in the financial sector can be helpful for stability and development. There is now evidence that, for example, lending by state-owned banks has helped in mitigating the impact of the crisis on aggregate credit. But evidence also points to negative longer-term effects of direct interventions on resource allocation and quality of intermediation. This suggests a need to rebalance the state's roles from direct to less direct involvement, as the crisis subsides. The state does have very important roles, especially in providing well-defined regulations and enforcing them, ensuring healthy competition, and strengthening financial infrastructure. One of the crisis lessons is the importance of getting the basics right first: countries with complex but poorly enforced regulations suffered more during the global crisis. Evidence also suggests that instead of restricting competition, the state needs to encourage contestability through healthy entry of well-capitalized institutions and timely exit of insolvent ones. There is also new evidence that supports the state's key role in promoting transparency of information and reducing counterparty risk. The challenge of financial sector policies is to better align private incentives with public interest, without taxing or subsidizing private risk-taking.